1987
DOI: 10.1080/15298668791384959
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Toxicity Studies With 1,3-Butadiene 3 Two Year Toxicity/Carcinogenicity Study in Rats

Abstract: Groups of 110 male and 110 female CD (Sprague-Dawley) rats were exposed to atmospheres containing 0 (control), 1000 or 8000 ppm v/v butadiene for 6 hr/day and 5 days/week. Ten of each sex from each group were killed at 52 weeks. The study was terminated when it was predicted that survival would drop to 20% to 25% (105 weeks for females and 111 weeks for males). High dose rats had wet, ruffled fur and showed slight incoordination during the first exposure each week. During the second year, mortality in both tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
126
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(127 citation statements)
references
References 0 publications
1
126
0
Order By: Relevance
“…Longterm inhalation exposure of mice and rats to BD caused development of tumors at multiple sites (1)(2)(3). BD is also considered a "Human Carcinogen" mostly because occupational exposure to BD has been associated with excess mortality from lymphatic and/or hematopoietic cancers (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Longterm inhalation exposure of mice and rats to BD caused development of tumors at multiple sites (1)(2)(3). BD is also considered a "Human Carcinogen" mostly because occupational exposure to BD has been associated with excess mortality from lymphatic and/or hematopoietic cancers (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Since the completion ofthe Meinhardt et al report (5), two animal inhalation bioassays have found 1,3-butadiene to be carcinogenic in rats (10) and in mice (11). Additionally, the findings of McMichael et al (4) prompted a more detailed case-referent study of these cancer deaths by Spirtas et al (12); this evaluation revealed an estimated relative risk of 2.4 for fatal lymphatic and hematopoietic malignancies associated with employment in the SBR production plant.…”
mentioning
confidence: 99%
“…This study was first reported in 1981 (30) and in the peerreviewed literature in 1987 (31). Male and female SpragueDawley rats, 100/group, were exposed to concentrations of 0, 1000, and 8000 ppm butadiene for 2 years (6 hr/day, 5 days/week).…”
Section: Carcinogenicitymentioning
confidence: 99%